Wind Drift Evaporation Loss and Soil Moisture Distribution under Sprinkler Irrigated Blackgram (Vigna mungo L.) - Arunadevi, K.; Nongkynrih, I.; Ramachandran, J. (International Journal of Bio-resource and Stress Management, 2021)
An experiment was conducted during March–June 2018 with the sprinkler irrigation system covered in an area of 39×42 m2. Proper design and management of sprinkler irrigation systems improves the uniformity of moisture distribution and reduces wind drift and evaporation losses (WDEL) for effective crop growth. Uniformity coefficient, wind drift and evaporation loss of the sprinkler system at a different pressure head of 2 kg cm-2, 2.5 kg cm-2 and 3 kg cm-2 were studied. Wind speed was observed by using handheld anemometer. The wind speed ranged between 0.9 to 4.5 m s-1. The highest uniformity coefficient of 88.19% and wind drift and evaporation loss of 3.5% were obtained at the pressure head of 3 kg cm-2 and the wind speed of 0.9 m s-1. Soil samples were collected at different depths of 0–10 cm, 10–20 cm, 20–30 cm and at a radial distance from 0 m, 3 m, 6 m, 9 m, 12 m respectively to determine the soil moisture distribution pattern. The soil moisture content values were plotted by using the computer software, surfer 10 of the windows version and contour maps were drawn. The moisture content was found to be more at 0–10 cm depth, as compared to 10–20 cm and 20–30 cm depth. The percentage of moisture was found to be highest at a 6 m distance, which was due to overlapping of the sprinkler system.